2010
DOI: 10.1104/pp.109.151704
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Ethylene-Responsive Element Binding Factor-Associated Amphiphilic Repression Motif-Containing Transcriptional Regulators in Arabidopsis

Abstract: The ethylene-responsive element binding factor-associated amphiphilic repression (EAR) motif is a transcriptional regulatory motif identified in members of the ethylene-responsive element binding factor, C2H2, and auxin/indole-3-acetic acid families of transcriptional regulators. Sequence comparison of the core EAR motif sites from these proteins revealed two distinct conservation patterns: LxLxL and DLNxxP. Proteins containing these motifs play key roles in diverse biological functions by negatively regulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
280
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 263 publications
(284 citation statements)
references
References 119 publications
(212 reference statements)
4
280
0
Order By: Relevance
“…The consensus sequence of the EAR motif was at first reported L/FDLNL/FxP in tobacco NtERF3, and in Arabidopsis AtERF3 and AtERF4 (Ohta et al 2001). Recently, Kagale et al (2010) reported two distinct conservation patterns of EAR motif (DLNxxP and LxLxL) and identified 219 EAR motif-containing proteins belonging to 21 different families in Arabidopsis. The LxLxL type of EAR motif was first reported in the SUPERMAN protein of Arabidopsis (Hiratsu et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The consensus sequence of the EAR motif was at first reported L/FDLNL/FxP in tobacco NtERF3, and in Arabidopsis AtERF3 and AtERF4 (Ohta et al 2001). Recently, Kagale et al (2010) reported two distinct conservation patterns of EAR motif (DLNxxP and LxLxL) and identified 219 EAR motif-containing proteins belonging to 21 different families in Arabidopsis. The LxLxL type of EAR motif was first reported in the SUPERMAN protein of Arabidopsis (Hiratsu et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…S6). Based upon a bioinformatics approach, the LxLxL motifs located between domains I and II have been predicted to be EAR-like repression domains in IAA7, IAA14, IAA16, and IAA17 proteins (Kagale et al, 2010). This second DLxLxL motif in IAA proteins is generally located at approximately 20 to 25 amino acids C terminal to the TELC/RLGLPG domain I motif.…”
Section: Discussionmentioning
confidence: 99%
“…Homologous sequences are present in monocots, although these lack the second zinc finger domain and putative NLS (Supplemental Figure 1). In addition to the zinc finger domains, we identified extended conservation around the CLLM motif and the tandem DLNxxP-and LxLxL-type EAR motifs at the C terminus ( Figure 1A) (Kagale et al, 2010).…”
Section: Daz1 and Daz2 Are Male Germline-specific Nuclear Proteins DImentioning
confidence: 99%